Pharmacoeconomic evaluation of providing pharmacist-managed anticoagulation service to patients on warfarin - Stojković Tatjana; Marinković Valentina; Lakić Dragana; Bogavac-Stanojević Nataša (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2016)
It has been determined that Pharmacist-Managed Anticoagulation Service (PMAS) for patients on warfarin improves anticoagulation control and decreases the rate of bleeding, thus reducing the overall health care costs. This study aims to compare the cost-effectiveness of providing pharmaceutical care (PC) and usual medical care (UMC) to patients on warfarin, from the perspective of the National Health Insurance Fund (NHIF) in Serbia. The cost-effectiveness analysis was conducted, with a time horizon of 10 days. Decision tree modeling combined data on efficacy from eligible studies, while the costs were taken from NHIF Drug and Service fee lists. Additionally, the budget impact analysis was performed, aiming to project annual savings by implementing PMAS as a part of anticoagulation clinics. PC has been perceived to be cost-effective strategy, since it enables a higher probability of well controlled INR value (additional effectiveness 0,154), along with lower costs (-374,51 RSD), compared to UMC. Negative incremental cost-effectiveness ratio additionally demonstrated cost-effectiveness of PC, as dominant strategy. Sensitivity analysis confirmed the model robustness, and budget impact analysis has also demonstrated significant annual savings, in the total amount of 50.863.313 RSD for a five year period 2016-2020. Providing PC to patients on warfarin represents a more cost-efficient strategy than UMS, in addition to better safety profile, which is why it should be implemented in the national health care system in the future.